Looking for an agreement: the mediating action of the Institute of Social Reforms (1903-1924) - Solana Alonso, Noelia (Revista de Historia Social y de las Mentalidades, 2026)
Throughout its career, the Institute of Social Reforms carried out significant work as an intermediary in the conflicts between employers and workers. Through the study of the internal documentation of the organization, among other sources, this paper examines how the institution implemented its intervention, the consequences it had, as well as the limitations it encountered in doing so. In this way, it will contribute to a better understanding of how the Instituto analyzed struggles related to the world of work, how it created spaces for dialogue, and the mediation strategies it used to address conflicts that threatened the consolidation of social reform
Keywords: Institute of Social Reforms; mediation; labour conflicts; strikes; social policy